A fracture mechanics-based approach to estimating the endurance limit of notched components. (January 2016) - Götz, S.; Ellmer, F.; Eulitz, K.-G.
Highlights: Support factors for notch sensitivity are calculated fracture mechanics-based. 3D surface cracks are modeled and evaluated directly in the notch of each component. An extensive database is used for validation and statistical evaluation. Abstract: The fatigue notch effect can be estimated by using fracture mechanics-based support factors. To do so, the SIFs for cracks in notches must be calculated. There is a problem of transferability when 2D reference geometries are used. This can be avoided by modelling 3D cracks in the part being assessed. As demonstrated in this study, this approach is more laborious but leads to better results. The proposed approach was validated using a broad database of different sintered steels. The statistical evaluation showed that the mean value was almost exactly predicted with a relatively small scatter compared to alternative approaches.